DNA methylation in intron 1 of the frataxin gene is related to GAA repeat length and age of onset in Friedreich ataxia patients. Issue 12 (12th August 2008) - Castaldo, I; Pinelli, M; Monticelli, A; Acquaviva, F; Giacchetti, M; Filla, A; Sacchetti, S; Keller, S; Avvedimento, V E; Chiariotti, L; Cocozza, S
Abstract : Background: The most frequent mutation of Friedreich ataxia (FRDA) is the abnormal expansion of a GAA repeat located within the first intron of FXN gene. It is known that the length of GAA is directly correlated with disease severity. The effect of mutation is a severe reduction of mRNA. Recently, a link among aberrant CpG methylation, chromatin organisation and GAA repeat was proposed. Methods: In this study, using pyrosequencing technology, we have performed a quantitative analysis of the methylation status of five CpG sites located within the region upstream of GAA repeat, in 67 FRDA patients. Results: We confirm previous observation about differences in the methylation degree between FRDA individuals and controls. We showed a direct correlation between CpG methylation and triplet expansion size. Significant differences were found for each CpG tested (ANOVA p<0.001). These differences were largest for CpG1 and CpG2: 84.45% and 76.80%, respectively, in FRDA patients compared to 19.65% and 23.34% in the controls. Most importantly, we found a strong inverse correlation between CpG2 methylation degree and age of onset (Spearman's ρ  =  −0.550, p<0.001). Conclusion: Because epigenetic changes may cause or contribute to gene silencing, our data may have relevance for the therapeutic approach to FRDA. Since the analysis can be performed in peripheral blood leucocytes (PBL), evaluation of the methylation status of specific CpG sites in FRDA patients could be a convenient biomarker.